Filtragem constitucional da colaboração premiada: Da necessária compatibilização com os direitos fundamentais - PAULO ADAIAS CARVALHO AFONSO (2022)
The award-winning collaboration regulated by Law n.º 12.850/13 brought great impact to the Brazilian criminal procedure, being essential for its effectiveness the constitutional filtering, especially regarding the respect for fundamental rights. This is because the 1988 Constitution represents a civilizing milestone, incorporating into the Brazilian legal system several fundamental guarantees hitherto the object of International Treaties, with the legislation before and after it receiving a compatibility check in order to be admitted. The work has the general objective of tracing the evolution of award-winning collaboration in Brazil, contextualizing historical moments of the period and external influences. Next, highlighting the importance that Operation Car Wash had in generating empirical controversies on the subject, we seek to highlight specific points for comparing the applied solutions, in particular regarding compatibility with due process of law, ample defense, the contradictory, the presumption of non-culpability and the right to silence. The work must use the bibliographic research procedure, in particular on scientific articles, books, jurisprudence, international treaties and internal legislation, as well as award-winning collaboration agreements signed in the course of Operation Car Wash, which help to understand the conventional historical evolution, legislative and jurisprudential institute in Brazil. The approach will be divided into two fronts. The first, of a dogmatic nature, will rely on a qualitative analysis of the main texts relevant to the theme, with exploratory objectives for adequate deepening on the relevant points. The second, of an empirical nature, will look for elements in which the process of Operation Car Wash contributed to the adequate constitutional filtering of the awarded collaboration. Bearing in mind that the approach starts primarily from the analysis of cases of award-winning collaboration in that operation and its effects on the constitutional and criminal procedural system as a whole, the research will adopt inductive reasoning. As a result, we seek to evaluate two specific controversial points of the operation. The first is the possibility of the agreement guaranteeing the employee access to property potentially proceeds or proceeds from the crime depending on the success of his collaboration, in what is conventionally called a “performance clause”. The second is the structural change caused by the presence of the whistleblower and the accused person as defendants in the same criminal action, whether due to the limit of the waiver of the right to remain silent, the contractual benefits to third parties or the need to reinterpret the legal procedure provided for in the procedural process.